2019
DOI: 10.1002/adma.201806095
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature In Situ Amino Functionalization of TiO2 Nanoparticles Sharpens Electron Management Achieving over 21% Efficient Planar Perovskite Solar Cells

Abstract: Titanium oxide (TiO2) has been commonly used as an electron transport layer (ETL) of regular‐structure perovskite solar cells (PSCs), and so far the reported PSC devices with power conversion efficiencies (PCEs) over 21% are mostly based on mesoporous structures containing an indispensable mesoporous TiO2 layer. However, a high temperature annealing (over 450 °C) treatment is mandatory, which is incompatible with low‐cost fabrication and flexible devices. Herein, a facile one‐step, low‐temperature, nonhydrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
184
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 224 publications
(195 citation statements)
references
References 59 publications
11
184
0
Order By: Relevance
“…For the pristine TiO 2 thin film, the O 1s core level could be deconvoluted into two peaks centered at 530.3 and 532.6 eV, respectively. The former peak (530.3 eV) was assigned to be the O 2− anion bonded with the Ti 4+ cation (TiO) in the stoichiometric TiO 2 structure, and the latter one (532.6 eV) represented the hydroxyl groups on the surface of TiO 2 film (TiOH) . After TiO 2 substrate was treated with ATPA, the peak intensity of TiOH was significantly reduced and a new peak appeared at 532.0 eV, indicating the formation of COTi bonds .…”
Section: Best and Average (Reverse Scan) Pv Parameters Measured In Rementioning
confidence: 99%
See 3 more Smart Citations
“…For the pristine TiO 2 thin film, the O 1s core level could be deconvoluted into two peaks centered at 530.3 and 532.6 eV, respectively. The former peak (530.3 eV) was assigned to be the O 2− anion bonded with the Ti 4+ cation (TiO) in the stoichiometric TiO 2 structure, and the latter one (532.6 eV) represented the hydroxyl groups on the surface of TiO 2 film (TiOH) . After TiO 2 substrate was treated with ATPA, the peak intensity of TiOH was significantly reduced and a new peak appeared at 532.0 eV, indicating the formation of COTi bonds .…”
Section: Best and Average (Reverse Scan) Pv Parameters Measured In Rementioning
confidence: 99%
“…These results implied that the esterification between the hydroxyl groups on TiO 2 surface and the carboxylic acid groups on ATPA occurred. Furthermore, the peaks of Ti 2 p 1/2 (459.2 eV) and Ti 2 p 3/2 (464.9 eV) changed little before and after the ATPA treatment (Figure S7, Supporting Information), indicating negligible influence of the reaction between TiO 2 and ATPA on the valence state of Ti. Considering that XPS could only probe the chemical states of top surface and the ATPA layer was sandwiched between TiO 2 and CsPbI 3 , we could only probe the interaction between the CsPbI 3 film and ATPA by spin‐coating a thin layer of ATPA onto the CsPbI 3 film and measured with XPS.…”
Section: Best and Average (Reverse Scan) Pv Parameters Measured In Rementioning
confidence: 99%
See 2 more Smart Citations
“…To solve these problems, doping and surface modifications have been widely researched in recent years. Hu et al [22] reported that upon applying NH 2 -TiO 2 nanoparticles as a novel ETL in the low-temperature process, the regular-structure PSCs exhibited a significant PCE improvement to over 21%. Liu and coworkers [23] introduced zinc ions into a compact TiO 2 lattice by a simple low-temperature solution process, which improved the interfacial carrier extraction between the ETL and perovskite, obtaining a PCE of 19.04% with 4.5% Zn-doped ETL PSCs.…”
Section: Introductionmentioning
confidence: 99%